Managing native fish communities during a long‐term drought. Issue 4 (25th January 2017) - Baumgartner, Lee J.; Wooden, Ian J.; Conallin, John; Robinson, Wayne; Thiem, Jason D.
Abstract: Ecological communities are adapted to extreme hydrological conditions. River regulation can, at times, exacerbate stressors such as drought and flood that threaten population persistence. Conversely, river infrastructure offers a means to deliver water for environmental benefit. Thus knowledge of the life history requirements of native fish, including location‐specific community structure during drought conditions, is required to inform the management of aquatic ecosystems for native fish in regulated systems. During a severe drought, fish community sampling at 30 sites was undertaken in the Edward–Wakool (E–W) river system, an anabranch system of the Murray River, southeast Australia, to provide recommendations into the current management under drought and for future planning. Fish from the E–W system demonstrated diverse responses to drought conditions. Some species recruited under drought conditions, whilst others were restricted in distribution to a few key refuge habitats. The ability for fish species to persist in the long term depends largely on developing appropriate management strategies that both protect critical habitat and sustain biological function. Both situations require a combination of advance planning and reactionary monitoring, which is adaptively used to minimise impacts. Here, we present a number of practical solutions, based on experience from the E–W system, that are applicable to other regulated river systems. It is essential that agencies responsible for drought management ensure appropriate plans are developed ready for implementation in advance of future drought events.